Clinical significance of primary symptoms in women with placental abruption. (17th September 2018) - Mei, Youwen; Lin, Yonghong
Abstract: Background: To evaluate the clinical significance of primary symptoms in women with placental abruption. Methods: A retrospective study of 273 cases of placental abruption was performed. The subjects were classified into two groups according to primary symptoms: 210 cases of the vaginal bleeding group and 63 cases of the abdominal pain group. The clinical features, maternal and neonatal outcomes were compared between two groups. Results: The incidence of preeclampsia and preterm birth in the vaginal bleeding group was significantly lower than abdominal pain group, while the incidence of premature rupture of membrane (PROM) in the former group was higher than that in the latter group. Both fetal and maternal outcomes were significantly poorer in the abdominal pain group than in the vaginal bleeding group in terms of rate of abnormal fetal heart monitoring (FHR), concealed abruption, abruption area over 50%, uteroplacental apoplexy, volume of postpartum hemorrhage, rate of blood transfusion, neonatal asphyxia and acidemia. Conclusions: Primary symptoms of placental abruption were associated with preterm birth, preeclampsia and PROM, which could predict pregnancy outcomes effectively.